EFFECT OF FIXED ORTHODONTIC APPLIANCES ON THE SALIVARY pH - Aslam, Abida; Naeem, Amjad; Abbas, Qalab; Amjad, Muhammad (Pakistan Armed Forces Medical Journal, 2011)
Objective: To assess the influence of fixed orthodontic appliances on the salivary pH. Study design: Randomized controlled trial. Place and duration of study: Department of Orthodontics, Armed Forces Institute of Dentistry in collaboration with the Department of Microbiology, Armed Forces Institute of Pathology Rawalpindi, from 10th September 2007 to 06th November 2008. Patients and Methods: Sixty Subjects (11 males and 49 females) with age ranging 13-20 years were randomly selected and divided into a control and an experimental group of 30 each. Study involved analysis of salivary samples. A proforma indicating salivary levels of pH at T1 (pre treatment) and at T2 (after 4 months) with the differences between T1 and T2 was prepared for each subject. Results: In experimental group salivary pH depicted a statistically significant decrease between T1 and T2. These changes in control group were insignificant. Conclusions: Fixed orthodontic appliances (FOAs) tend to influence oral environment by lowering salivary pH towards acidic side.